Synthesis of Novel and Complex Tetrahydroquinazolinedione and Dihydropyrido[2,3-d]pyrimidine Derivatives via a One-Pot [4+2]-Cycloadddition Strategy - Sarmah, Manas M.; Prajapati, Dipak; Hu, Wenhao (Synlett, 2013)
A mild and efficient protocol for the synthesis of various tetrahydroquinazolinedione and dihydropyrido[2,3-d]pyrimidine-2,4-dione templates from uracil derivatives utilizing a [4+2]-cycloaddition strategy in a one-pot reaction has been developed.
Keywords: zwitterionic species; phase-transfer conditions; tetrahydroquinazolinediones; dihydropyrido[2,3-d]pyrimidines